Digital transitions at the port: human capital, technology adoption and operational efficiency among independent truckers - George Acheampong; Oliver Kwabena Aggrey; Alfred Kwadwo Yamoah Djan; Annette Skovsted Hansen; Mmakgabo Pinkie Segodi (Innovation & Management Review, 2025)
In this study we seek to understand the relationship between a trucker's level of human capital, their ease of use of new technology innovations and how this translates into overall port efficiency at the Port of Tema.To perform this inquiry, we develop a five-construct framework with trucker's self-efficacy and mentorship moderating relationship between human capital, perceived ease of use (PEOU) of new technology innovations and port efficiency. We utilize a structural equation model (SEM) to analyze data retrieved from 174 independent truckers at the Tema Port.We find significant relationships between a trucker's human capital variables such as education, skills and training and PEOU, which in turn had effects on efficiency. We also interestingly found that truckers with a higher self-efficacy did not necessarily transition faster with use of the new technologies and those that received mentoring support had varying effects on ease of use of new technology.We present new and interesting evidence on the new technology innovations at the port, their perceived assimilation into the relatively lowly-educated workforce and how these antecedents affect perceived operational efficiency in a unique African and port context.
Keywords: 650; Human capital; Innovation adoption; Port efficiency; Mentoring; Self-efficacy; Africa